Integrating circuit training into physical education: effects on javelin throwing performance in junior high school students - Mappanyukki, Andi Atssam; Anwar, Nur Indah Atifah; Sarifin; Aksir, Muh Ilham; Hamzah, Alimin (Journal Sport Area, 2026)
Background: Javelin throwing is a complex athletic skill that requires strength, speed, balance, and proper release mechanics. In school settings, many students struggle to master these fundamentals due to limited practice time, lack of effective learning media, and insufficient development of the physical abilities needed to support throwing performance. Objectives: This study aimed to examine the association between circuit training and improvements in javelin throwing performance among junior high school students. Methods: A quasi-experimental one-group pretest–posttest design was employed involving 60 junior high school students in Makassar. Javelin throwing performance was assessed using a validated rubric covering technique, power, distance, and rule compliance. An eight-week circuit training programme was implemented, and data were analysed using descriptive statistics and paired-samples t-tests. Results: The findings showed that the mean javelin throwing score increased from 73.00 ± 13.72 (pretest) to 82.10 ± 13.28 (posttest). Paired-samples t-test results indicated a statistically significant difference (t(59) = -20.83, p < 0.001), with a mean improvement of 9.10 points and a moderate-to-large effect size (Cohen’s d = 0.68). This magnitude suggests a practically meaningful improvement in students’ throwing performance within a school-based context. Conclusion: Circuit training was associated with improvements in javelin throwing performance and shows potential as an instructional strategy in physical education. However, the absence of a control group limits causal inference, and future research should employ controlled designs to confirm these findings and examine long-term skill retention. Practically, the results support the use of structured circuit-based activities to optimise limited instructional time in school physical education settings.